The Origins of War in Mozambique : A History of Unity and Division - Funada-Classen, Sayaka (Book collections on Project MUSE., 2013)
The book focuses on an area called Maúa, not because I believe Maúa represents the whole of Mozambique as such, but because highlighting a specific area and people helps to understand the Mozambican history more deeply and comprehensively. In any case, it would be impossible to study the experience of all Mozambicans. I am not attempting to write a history textbook of Mozambique, or a glorious history of the liberation struggle, but rather trying to fill a gap in the descriptions of contemporary Mozambican history by delving into matters that have not been written about before.